Pengaruh SIA Terhadap Kualitas Laporan Keuangan Desa Dengan Kompetensi SDM Sebagai Mediasi di Kabupaten Tanah Laut - Bandi, Maulida Hirdianti; Fitriyani, Yuli; Amelia, Noor (Institut Agama Islam Negeri (IAIN) Madura, 2025)
This research was conducted with the aim of analyzing and testing the influence of accounting information systems on the quality of village financial reports with human resource competency as mediation. The method and analysis used in this research is a quantitative descriptive method by distributing questionnaires and processing them using SmartPLS version 3 software. The data collection technique in this research uses a questionnaire technique, namely data collection is carried out by giving a set of questions or written statements to the respondent, namely the village financial treasurer. . The population in this study is the village government in 6 sub-districts in Tanah Laut Regency, totaling 75 villages consisting of 9 villages in Bajuin District, 20 villages in Pelaihari District, 14 villages in Bati-Bati District, 11 villages in Kurau District, 9 villages in Tambang Lagi sub-district and 12 villages in Takisung sub-district, and also using documentation techniques taken from archives owned by the village government or other respondents who are considered capable of providing significant data regarding the research object. The research results obtained are that the Accounting Information System (X) has a significant effect on the Quality of Village Financial Reports (Y) through HR Competency (Z), this can be explained by the use of IT in making it, not necessarily the final solution to the quality of regional financial reports, but it must be followed by HR competencies that will benefit from IT.